PENALARAN KUANTITATIF SISWA SMA DALAM MENYELESAIKAN SOAL ESSAY MATERI TRIGONOMETRI - Fransiska Tampubolon; Edy Yusmin; Dian Ahmad (Universitas Tanjungpura, 2020)
AbstractThis study aims to analyze the quantitative reasoning of senior high school students in essay test of trigonometric subject matter. Quantitative reasoning that emphasizes the effective involvement of life and daily work in solving problems makes quantitative reasoning in accordance with the demands of the 2013 curriculum which is based on constructivism curriculum. Students have quantitative reasoning if they have six aspects of ability. The six aspects are representation, interpretation, calculation, analysis, communication and assumptions. This research uses descriptive exploratory methods and with case study research. Data collection uses essay test questions with trigonometric material and interview guide sheets. Six students were chosen with different abilities, namely high, medium and low. After conducting research on the six children, it can be concluded that in general students do not have good quantitative reasoning. this is because the six children examined have not been able to fulfill all six aspects of quantitative reasoning, especially the aspects of student is communication are classified as very low with a percentage of 0%.Keywords: Essay Test, Quantitative Reasoning, Trigonometric